THE EFFECT OF PRODUCT AVAILABILITY, SELLING PRICE AND SERVICE ON THE PURCHASE DECISION OF SEMEN PADANG PRODUCTS AT REZA BUILDING SHOP IN AIRTIRIS - Diki Jandri; Auzar Ali; Muhammad Salis; Royansyah Putra (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to determine how the influence of product availability, selling price and service simultaneously and partially on the purchasing decisions of Padang cement products at the Reza Bangunan Store in Airtiris. The population in this study were all consumers recorded in July 2021, namely as many as 247 consumers. The sample in this study was determined using the Slovin formula so that as many as 71 respondents were obtained. Data analysis was performed using multiple linear regression model. Based on the results of simultaneous hypothesis testing, the variables of product availability, selling price and service are proven to have a joint effect on purchasing decisions for Padang cement products at the Reza Bangunan Store in Airtiris. Based on the results of partial hypothesis testing, the variables of product availability, selling price and service are proven to have an individual effect on the purchasing decision of Padang cement products at the Reza Bangunan Store in Airtiris, with the service variable as the dominant variable that influences purchasing decisions. The close relationship between the variables of product availability, selling price and service on purchasing decisions is very strong with a correlation coefficient (R) of 95.8%. While the contribution of product availability, selling prices and services to purchasing decisions is 91.5% while the remaining 8.5% is influenced by other variables not examined in this study.